(3cJGH CUd GdCUhd aj NhGU GdfLhe hCMcGegG hCMcGe GdehGdjOs - (3CHh GdYfHS GdUjeQj,J (B275 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi GdeMGeO GdaGNQI bGd CHh GdYfHS GdUjeQi hhLOJ gPG GdYde GdTQja TLQJg GdMSGH haQhYg eYQaI Gdadc s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: 13 (3SfI TQaI ai NeS YTQI OQLI ef GdSfHdg gHhWg ai NeS YTQI ai ebGHdI HjJg aYdg JOHjQ CeQ GdehdhO ai GdQMef ai GdTgQ GdSGOS hJhdjO GdLdO MJi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B107s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs